Implementation of the Cooperative Learning Model in Arts and Culture Subjects in Elementary Schools - Ridwan, Ridwan; Arzani, M.; Sukarto, Sukarto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine the planning, implementation and impact of the jigsaw type cooperative learning model on class V arts and culture subjects at SDN 1 Gumantar. The research subjects were the principal and teachers of arts and culture subjects. The research instruments are in the form of observation guidelines, interview guidelines and documentation guidelines that measure planning, implementation and impacts produced using the jigsaw type cooperative learning model in arts and culture subjects. Data collection techniques in this research used observation, interviews and documentation. Data analysis techniques are carried out using Data Reduction, Data Display (data presentation), Conclusion Drawing/Verification (drawing conclusions and verifying). There are various kinds of learning models that can be implemented in a learning activity. One of them is the jigsaw type cooperative learning model which is a learning model where students can learn to collaborate, work together and be responsible for understanding certain material and conveying it to their group friends. So that when implementing the jigsaw type cooperative learning model in arts and culture subjects, learning activities can indirectly foster the value of student cooperation. The objectives of this research are as follows: 1) to describe the planning of the jigsaw type cooperative learning model in arts and culture subjects, 2) to describe the jigsaw type cooperative learning model in arts and culture subjects, 3) to describe the impact of the jigsaw type cooperative learning model on The 11th unit of visual arts material culture lesson is making works of art from recycled household waste materials.